ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PERUSAHAAN JASA YANG TERDAFTAR DI BEI (Studi kasus pada perusahaan jasa sektor infrasturktur, utilitas dan transportasi tahun 2015-2018) - Arina Kusumawati (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to analyze and provide empirical evidence regarding the effect of growth opportunity, firms size, leverage, net working capital, profitability and the BI rate on the cash holding services company in the infrastructure, utilities and transportation sectors in 2015-2018. The sample in this study was obtained using a purposive sampling method. Based on the criteria, 21 companies were selected as the research sample. The analytical method used is multiple linear regression analysis.The results of the study show that there is a positive influence between the growth opportunity, profitability and BI rate on cash holding and also a negative influence between firms size and leverage on cash holding. Net working capital has no influence on cash holding. Keyword : cash holding, growth opportunity, firms size, leverage, net workingcapital, profitability, BI rate.